The Makinaugalingon an index to Iloilo's historical past in relation to national and world events, 1913-1941 - Piamonte, Rosalinda P.; De Castro, Lourdes V.; Picache, Ursula G. (Quezon City : Institute of Library Science, University of the Philippines Diliman, 1980)
This is an index to all issues of Makinaugalingon, a newspaper published in Iloilo from 1913-1941. During this period, several vernacular newspapers came out but it was only the Makinaugalingon which stayed longest in the scene. Responsible for its publication was a nationalistic man and writer, Rosendo Mejica who was a respected name and political figure in Iloilo during those times.
The index is divided into parts. The first part is the Author Index which includes an alphabetical listing of authors of news, essays, poems, short stories, speeches, songs, zarzuelas and dramas. Following each author's name are their works arranged in alphabetical order by the first word of the title. Initial articles are disregarded, with an indication in brackets of the literary form of the entry, followed by the page, column and date of publication. The second part is the Subject Index with entries arranged alphabetically. Each entry includes the subject heading, title of the article in the Hiligaynon language or a summary of the news in English followed by its author, page, column, date of publication, and an indication whether the entry is an editorial, speech, or any type of illustration.
Mimeographed.
Special Problem (Master of Library Science)--University of the Philippines Diliman
Keywords: Hiligaynon newspapers -- Indexes; Makinaugalingon (Periodical).